TV launches 24-hour news with CNN : an augmented reading experience - Burgan, Michael (Captured television history., 2020)
Investigates the origins of the twenty-four-hour news cycle, beginning with CNN in 1980, when Ted Turner changed the way TV programming was done forever. Highlights Bernie Shaw's coverage of the Gulf War and how it made CNN an internationally known organization. Includes a glossary.